A study on bid-ask spread patterns of Nikkei 225 stock index futures traded on SGX-DT and OSE. - Goh, Jimmy. (2008)
This project is to conduct a comparative study of the bid-ask spreads of Nikkei 225 stock index futures that are traded on both Singapore Exchange Derivative Trading Limited (SGX-DT) and Osaka Exchange (OSE).